THE EFFECT OF RHEUMATIC GYMNASTICS ON JOINT PAIN IN OSTEOARTHRITIS PATIENTS - Bitcar, Bitcar; Agustian, Irwan; Pasaribu, Masdalifa; Lubis, Cherida (Jurnal Keperawatan Respati Yogyakarta, 2022)
Osteoarthritis is a disease characterized by joint pain. For this reason, non-pharmacological interventions for rheumatic exercises are needed regularly and routinely to reduce joint pain. This study aims to determine the effect of rheumatic exercise on joint pain in patients with osteoarthritis. Type of research is a pre-experimental design with a One Group Pretest – Posttest approach. The study population was patients with osteoarthritis. The sampling used is non-probability sampling with Accidental Sampling technique, the number of samples as many as 27 people. The research instrument used rheumatic gymnastics SOP and pain instrument with a numeric rating scale. Data analysis using the Wilcoxon test. The results showed that the patient's joint pain before rheumatic exercise was moderate pain average pain scale 4.70, after rheumatic exercise the joint pain experienced mild pain with average scale 3.63. The results of the statistical test showed that the p-value was 0.012 < (0.05), so the research hypothesis was accepted. The conclusion of the study showed that there was an effect of rheumatic exercise on joint pain in patients with osteoarthritis. It is hoped that health workers can apply rheumatic exercise therapy as an alternative to non-pharmacological therapy in reducing joint pain in patients with osteoarthritis.   Keywords: Rheumatic gymnastics; Joint pain; Osteoarthritis